Pigmented Gastropods-Assosiate Bacteria: an Innovation in Natural Antioxidants, Antibacterials, and Sun Protection - Hanif, Marwa Irfan; Pringgenies, Delianis; Setyati, Wilis Ari (Bogor Agricultural University, Indonesia, 2025)
This research investigates the ocean's potential as a source of natural active ingredients with antioxidant, antibacterial, and sun protection properties. Marine gastropods are known to have symbiotic relationships with associated bacteria capable of producing pigments, which hold promise for the cosmetic and health sectors. The study aims to identify and analyze pigments produced by bacteria linked to marine gastropods and evaluate their effectiveness as antioxidants, antibacterials, and sun protectants. The method involved isolating and analyzing pigments from gastropod-associated bacteria, followed by tests to assess their properties. Results revealed two gastropod species: Telescopium telescopium (Linnaeus, 1758) and Cassidula nucleus (Gmelin, 1791), from which 21 bacterial isolates were obtained—10 from T. telescopium and 11 from C. nucleus. Among these, Micrococcus yunnanensis, a bacterium with high pigment production, was successfully isolated. At 1,000 µg/mL, its pigment's crude extract had low antioxidant activity and had a low SPF category as a photoprotective agent. Antibacterial tests showed efficacy against Pseudomonas aeruginosa and Staphylococcus aureus. HPLC and FTIR analysis suggested the pigment contains carotenoid compounds. These findings highlight the potential of M. yunnanensis pigment for sustainable health and cosmetic applications.